A case study of male tawny owl (Strix aluco) vocalizations in South Korea: call feature, individuality, and the potential use for census. Issue 2 (4th March 2019) - Choi, Wonsuk; Lee, Ju-Hyun; Sung, Ha-Cheol
ABSTRACT: Vocal individuality has been used as a monitoring tool, and two criteria are a prerequisite: high variation among individuals and low variation within individuals, and vocal consistency within and across seasons. We examined individual variation in the territorial hoot calls of the tawny owl ( Strix aluco ) to discriminate between males and to assess a possible conservation technique that would allow for monitoring individuals within a study area. The territorial calls were recorded from five males in the Naejang Mountain National Park in South Korea during the breeding season in 2015 and 2016 and analyzed both quantitatively and qualitatively to determine the amount of variation within and between individuals. Our results showed that the territorial calls were specific to individuals within a population and that the acoustic distances between males living in the same territory during the two years were the smallest for the four nesting sites. Our results suggest that territorial calls of the tawny owls are individually identifiable over two years and that this acoustic technique can be useful for monitoring individual site fidelity.